Activity assay based on the immobilized enzyme kallikrein and mass spectrometry - Carvalho, Daniella Romano De; Laurentino, Bruna Barbosa; Rocha, Camila Loreta; Kool, Jeroen; Somsen, Govert; Amstalden van Hove, Erika; Cardoso, Carmen Lúcia (Frontiers in Analytical Science, 2022)
Deregulated activity and expression of human kallikreins (KLKs) may be involved in various pathologies, so these enzymes are an attractive biological target for identifying molecules that can modulate KLK activity. This identification involves applying fast and efficient screening methods. This work describes an off-line assay with mass spectrometry (MS) detection that uses KLK immobilized on Sepharose-NHS as a micro-column configuration (IMER-KLK-Sepharose-NHS). The mass spectrometry used has an ion trap analyzer and electrospray ionization (EIS). The HPLC-MS method for quantifying KLK activity was developed. The enzymatic assay conditions were optimized, and the IMER-KLK-Sepharose-NHS kinetic parameter (KMapp = 15.48 ± 3 μmol L-1) was evaluated. Finally, the method was validated by using leupeptin as a reference inhibitor (IC50 = 0.85 ± 0.10 µmol L-1). The developed method was able to identify the reference inhibitor and can be an alternative for screening KLK inhibitors